(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Response surface methodology (RSM) was used to optimise the microencapsulation process of Citrus Hystrix L. Oil (CHO) by depressurization of an expanded liquid organic solution (DELOS) sub and supercritical CO2. The particle size and yield (%) was studied with considered to three key factors variables including pressure (30-80 bar), temperature (40-60ËšC) and resident time (10-60 minutes) on the microencapsulation process. The optimum result from RSM is 549.4 nanometer for the particle size and 38.193% yield at optimum pressure 54.14bar, temperature 59.65ËšC and resident time 58 minutes. The results clearly show that the interactions between pressure, temperature and time have a significant effect on the microencapsulation process. Thus, the microencapsulated formulation has potential to be applied to other volatile compounds.